Vascular function after acute aerobic exercise in adults with and without type 2 diabetes mellitus - João Luís Marôco; Inês Arrais; Tiago Silvestre; Marco Pinto; Sérgio Laranjo; João Magalhães; Helena Santa-Clara; Bo Fernhall; Xavier Melo (Scientific Reports)
Abstract It is unknown whether type 2 diabetes mellitus (T2DM) influences the vascular function response to aerobic exercise. We examined brachial artery flow-mediated dilation (FMD) and flow-mediated slowing (FMS) of pulse wave velocity (PWV), 10-and 60-min after a high-intensity interval exercise (HIIE) and moderate-intensity continuous exercise (MICE) in adults with and without T2DM. Twelve older male adults with T2DM (57–84 years), and twenty-four healthy young and older adults (12 per group, aged 20–40 years and 57–76 years, respectively), completed an acute bout of HIIE, MICE, and a non-exercise condition. FMD was evaluated by the same researcher following standardized guidelines. FMS was calculated from the manufacturer’s PWV beta formulas. Central arterial stiffness was estimated via carotid-femoral PWV (cfPWV). %FMD was reduced (d= − 5.94%, 95% CI: − 10.50 to − 1.38%, p = 0.002), whereas %FMS increased (d = 4.55%, 95% CI: 0.62 to 8.48%, p = 0.01), 10-min after HIIE only in adults with T2DM, normalizing 60-min into recovery. Conversely, %FMD was increased (d = 5.33%, 95% CI: 0.76 to 9.89%, p = 0.009) 10-min after MICE only in adults with T2DM. cfPWV remained unchanged following HIIE and MICE in all groups. We report disease-associated vascular function responses to aerobic exercise suggesting both HIIE and MICE uncover transient vascular alterations in older adults with T2DM.